Preparation of biodiesel from waste cooking oil via two step batch catalyzed process with the aid of acid sulfuric and sodium hydroxide as the catalyst - Wan Jasrina, Wan Abd Ghani (2008)
With environmental and energy source concerns on the rise, using agricultural fats and biological sources as fuel in diesel engines has captured increasing attention. Biodiesel has many advantages relative to petroleum. It has several processes that can be used in producing biodiesel but transesterification is the most commonly used in industry. In transesterification, it involved reaction between tryglycerides from waste cooking oil and methanol to produce biodiesel. The catalysts used in this experiment were acid sulfuric and sodium hydroxide catalyst. Two step catalyzed was chosen to be used in preparation biodiesel from waste cooking oil because the free fatty acid content was high in waste cooking oil. For the first step, the molar ratio used was 10:1 with the presence of 2 wt% of H 2SO4 as catalyst with the temperature was 95oC and 4 hours of reaction time. For the second step, the molar ratio used was 6:1 with the presence of 0.2, 0.4, 0.6, 0.8 and 1wt% of NaOH as catalyst with the temperature were 40,50,60,70, 80oC and 1 hour of reaction time. Then, the biodiesel have to analyse by titration method to check free fatty acid and acid value content. It is proved that, this method can remove both free fatty acid and acid value up to 95%. This study also has indicated that the main factors that affect the reaction are reaction temperature and catalyst concentration.